Psychology applied to work - Muchinsky, Paul M. (Australlia, 2007)
In every chapter I have a special feature entitled Cross-Cultural I/O Psychology that explains or illustrates global applications of the material in the chapter. I have also included a special feature entitled The Changing Nature of Work in every chapter that reflects the latest issues associated with I/O psychology.
Keywords: Industrial Psychology